Analisis Tanggung Gugat Pemerintah Dalam Perlindungan Data Pribadi Pada Aplikasi Kesehatan Berbasis Digital - Virga Al Farichi (Future Academia : The Journal of Multidisciplinary Research on Scientific and Advanced, 2025)
The purpose of this research is to provide an explanation and find out whether a country or government can be sued if it fails to provide protection for personal data. In writing this journal article, the researcher used a normative juridical method with a statutory approach and a conceptual approach equipped with legal materials in the form of primary legal regulations and secondary in the form of scientific articles and books. The results obtained from this research are that the state/government will be held accountable if it fails to provide protection for personal data in the case of digital-based health applications. This can be seen from the Personal Data Protection Law which states the rights of personal data subjects to lawsuits and to receive compensation for violations in the personal data processed. However, provisions regarding compensation procedures have not been further regulated in government regulations implementing the Personal Data Protection Law.